A Feasibility Study of The Bubon Port to Improve Maritime Affairs in West Aceh District - Zakia Zakia; Meylis Safriani; Delfian Masrura; Dian Febrianti; Inseun Yuri Salena (Master Program of Information Technology, Universitas Malikussaleh, Aceh Utara, Indonesia, 2023)
Kuala Bubon Port, a maritime axis in the west-south Aceh region is one of the crossing facilities that connects shipping activities by the surrounding community. The need for passenger departures and logistics transportation is increasing every year. Therefore, to facilitate inter-island crossing activities, it is planned to develop buildings and facilities at Kuala Bubon Port. It is necessary to carry out a feasibility study for these infrastructure development activities to determine the feasibility of the development project. Besides that, the feasibility study also avoids the risk of loss. Research This feasibility study uses data analysis, including the Budget Plan analysis and the cash flow (cash flow) analysis. The method for analyzing cash flow uses 4 methods, namely Net Present Value (NPV), Benefit Cost Ratio (BCR), Internal Rate of Return (IRR), and Break Event Point (BEP). The four methods refer to the calculation of direct, indirect, and annual costs. This calculation is obtained from processing primary and secondary data and assuming an interest rate of 3.50%, and the project's economic life is set at 25 years. For NPV analysis, the investment is feasible if the results are positive. Conversely, if the NPV is negative, the investment is not feasible. Furthermore, if the BCR value ≥ 1, the IRR value ≥ the interest rate, and the BEP are obtained when the NPV = 0, then the project can be feasible. After calculating, the NPV value obtained is IDR 1,730,821,838,222, the BCR value is 162.93%, the IRR value is 5.25%, and the BEP was obtained in year 4, day 39. Based on the results of these calculations, the project can be said to be feasible to implement. The results of this study are expected to be one of the references and information for the Department of Transportation, Water Resources Public Works, and the Government to plan the right design for development projects at ports. The long-term target is that the results obtained can be used as data in other water construction projects so that they are effective from a financial perspective.